The Japanese Experience with Basic Fibroblast Growth Factor in Cutaneous Wound Management and Scar Prevention: A Systematic Review of Clinical and Biological Aspects - Mohamed Abdelhakim; Xunxun Lin; Rei Ogawa (Adis, Springer Healthcare, 2020)
Abstract Introduction Basic fibroblast growth factor (bFGF) plays several key roles in wound healing. Over the last 2 decades, clinical and basic research on bFGF has been actively conducted in Japan with reports on its potent efficacy in accelerating the healing of chronic ulcers and burn wounds by stimulating key cellular players in the skin. However, its efficacy remains unrecognized internationally. Thus, this study reviews current knowledge about the therapeutic value of bFGF in wound management and scar prevention accumulated in Japan over the last 2 decades. Methods We review the Japanese literature that demonstrates the anti-scarring effects of bFGF and exhaustively assess how these effects are exerted. Using the search terms "bFGF OR growth factors AND wound healing in Japan" and "bFGF AND scar prevention in Japan," we conducted a search of the PubMed database for publications on the role of bFGF in wound and scar management in Japan. All eligible papers published between 1988 and December 2019 were retrieved and reviewed. Results Our search yielded 208 articles; 82 were related to the application of bFGF for dermal wound healing in Japan. Of these, 27 fulfilled all inclusion criteria; 11 were laboratory studies, 7 were case reports, 4 were clinical studies, and 5 were randomized controlled trials. Conclusion Further research, with recognition of the therapeutic value of bFGF in wound and scar management and its clinical applications, is needed to provide additional clinical advantages while improving wound healing and reducing the risk of post-surgical scar formation.